Original paperThe importance of the implant quality in APBI – Gliwice experience. Dosimetric evaluation - Cholewka, Agnieszka; Szlag, Marta; Białas, Brygida; Kellas-Sleczka, Sylwia; Slosarek, Krzysztof (Journal of Contemporary Brachytherapy, 2013)
Purpose: This study covers four years of our clinical trials to improve implant quality in multicatheter Accelerated Partial Breast Irradiation (APBI). The progress made in dosimetric and volumetric parameters of the treatment plans was evaluated. Material and methods: One hundred and ninety-one women, for whom treatment plans were made based on three dimensional imaging, were selected for the study. To evaluate progress made in our APBI procedure, following parameters and indices were taken into account: percentage of the target volume receiving the reference dose (PTVref), minimum dose in the target volume expressed as a percentage of reference dose (PTVmin), dose homogeneity index (DHI) and conformity index (COIN). Additionally the plan quality index was calculated for every group as the sum of mean values of four evaluated parameters. Results: PTVref have increased from the mean value of 83.4% at the beginning to 94.8% recently. The maximum value equals 95.4%. The same trend can be observed with PTVmin value which has been improved from 51.7% to 70.1% maximally. DHI and COIN mean values present the similar progress. DHI value increased from 0.53 level to 0.68 and COIN from 0.58 in 2009 to 0.74. Plan quality index has increased from 2.46 in 2009 to 3.06 recently. Conclusions: The implant quality is crucial for the accurate dose distribution. This paper shows the progress we’ve made in APBI procedure to improve implant quality. Nowadays our implant technique based on three-dimensional CT imaging results in acceptable dose distributions.